Returning HIV‐1 viral load results to participant‐selected health facilities in national Population‐based HIV Impact Assessment (PHIA) household surveys in three sub‐Saharan African Countries, 2015 to 2016. (24th November 2017) - Saito, Suzue; Duong, Yen T; Metz, Melissa; Lee, Kiwon; Patel, Hetal; Sleeman, Katrina; Manjengwa, Julius; Ogollah, Francis M; Kasongo, Webster; Mitchell, Rick; Mugurungi, Owen; Chimbwandira, Frank; et al.
Abstract: Introduction: Logistical complexities of returning laboratory test results to participants have precluded most population‐based HIV surveys conducted in sub‐Saharan Africa from doing so. For HIV positive participants, this presents a missed opportunity for engagement into clinical care and improvement in health outcomes. The Population‐based HIV Impact Assessment (PHIA) surveys, which measure HIV incidence and the prevalence of viral load (VL) suppression in selected African countries, are returning VL results to health facilities specified by each HIV positive participant within eight weeks of collection. We describe the performance of the specimen and data management systems used to return VL results to PHIA participants in Zimbabwe, Malawi and Zambia. Methods: Consenting participants underwent home‐based counseling and HIV rapid testing as per national testing guidelines; all confirmed HIV positive participants had VL measured at a central laboratory on either the Roche CAP/CTM or Abbott m2000 platform. On a bi‐weekly basis, a dedicated data management team produced logs linking the VL test result with the participants' contact information and preferred health facility; project staff sent test results confidentially via project drivers, national courier systems, or electronically through an adapted short message service (SMS). Participants who provided cell phone numbers received SMS or phone call alerts regarding availability of VL results. Results and discussion: From 29, 634 households across the three countries, 78, 090 total participants 0 to 64 years in Zimbabwe and Malawi and 0 to 59 years in Zambia underwent blood draw and HIV testing. Of the 8391 total HIV positive participants identified, 8313 (99%) had VL tests performed and 8245 (99%) of these were returned to the selected health facilities. Of the 5979 VL results returned in Zimbabwe and Zambia, 85% were returned within the eight‐week goal with a median turnaround time of 48 days (IQR: 33 to 61). In Malawi, where exact return dates were unavailable all 2266 returnable results reached the health facilities by 11 weeks. Conclusions: The first three PHIA surveys returned the vast majority of VL results to each HIV positive participant's preferred health facility within the eight‐week target. Even in the absence of national VL monitoring systems, a system to return VL results from a population‐based survey is feasible, but it requires developing laboratory and data management systems and dedicated staff. These are likely important requirements to strengthen return of results systems in routine clinical care.